The contribution of Romanian pharmacists to public health by analysis of natural resources used in the treatment or prevention of various diseases - Taerel, Adriana Elena (Archives of Pharmacy, 2022)
The objective of the study is to mark the role of pharmacists in the analysis of spa resources from Romania. Identification and study of documents from the 19th-21st century. Romania is one of the richest countries in terms of natural resources that can be used for therapy: thermal and mineral water, mud, salty microclimate and the seaside. Some of these have been used empirically since ancient times. In the 18th and 19th centuries it took place theirs “rediscovery". By isolated initiatives or even by a concerted action, there were initiated scientific researches and some of these resources have been mapped. Having a good background in chemistry, pharmacists were involved together with physicians in the early stages that founded balneology as science. It can be mentioned pharmacists: C.C. Hepites, A. Trausch, S. Konya, A.N. Bernath Lendway. Carol Davila, organizer of medical and pharmaceutical education in Romania, himself encouraged the participation of students from the School of Medicine and Pharmacy to inquiry and use these resources for treatment or prevention of disease. This past and the fact that today the tourism of Romanian came under globalization, forces us to turn to account these spa᾽s resources that nature has given us. The pharmacists᾽ involvement in the analysis and the valorification of spa resources is a certainty.